Transmission of {332}〈113〉 twins across grain boundaries in a metastable β-titanium alloy. (June 2018) - Lin, Fengxiang; Marteleur, Matthieu; Jacques, Pascal J.; Delannay, Laurent
Abstract: Plastic deformation by dislocation slip and twinning is investigated in a metastable body centered cubic Ti-Mo alloy. Experimental crystal orientation maps show twin lamellae connected across grain boundaries, especially when they host low angle misorientation angles. A three-dimensional crystal plasticity based finite element model (CPFEM) is used to predict internal stresses due to deformation twinning. It is found that twin transmission across grain boundaries relaxes the strong back-stresses at the twin tip more than dislocation slip does. CPFEM predictions also indicate that the forward-stresses, which promote twinning in the adjacent grain, depend not only on the crystal misorientation angle but also on the misorientation axis, and the inclination of the grain boundary plane. Graphical abstract: Image 1 Abstract : According to EBSD, mechanical twins are often transmitted across grain boundaries in metastable β -titanium with bcc symmetry. CPFEM of 3D polycrystalline aggregates allows considering adjoining twin pairs with varying geometries and misorientations. CPFEM demonstrates that twin transmission across grain boundaries significantly relaxes internal stresses at the twin tip.